An International Classification of Function, Disability and Health (ICF)-based investigation of movement impairment in women with pelvic organ prolapse - Corlia Brandt; Elizabeth C. Janse van Vuuren (AOSIS, 2019)
Background: There is little evidence on movement impairment of the abdominal and pelvic floor muscles (PFM) in women with pelvic organ prolapse (POP). Objectives: The aim of this study was to determine the movement impairments and interactions between the PFM and abdominal muscles in POP. Method: The PFM and abdominal muscles of 100 conveniently sampled South African women with POP were assessed by ultrasonography, electromyography (EMG), the PERFECT scale, Sahrmann scale and a Pressure Biofeedback Unit (PBU). A demographic questionnaire determined contextual factors (exercise and medical history) and Visual Faces Scale pain intensities. Data were analysed descriptively and with Spearman and Pearson correlation coefficients. Results: Participants (59 ± 9.31 years) were mostly unemployed (80%), physically inactive (85%), with comorbidities, heart or vascular disease, hypothyroidism and depression. The mean levator hiatus at rest (56.38 mm, standard deviation [SD] 9.95), thickness (5.1 mm, SD 1.41), amount of movement (4.28 mm, SD 6.84), strength (level 1.89, SD 1.13) and endurance (4.04 s, SD 3.32) of the PFM indicated dysfunction. Median values of zero were found for the Sahrmann scale (interquartile [IQ] range [0-1]) and PBU (IQ range [0-2]) and 10.95 µV for abdominal EMG (IQ range [7.9-17.8]). Pelvic floor muscle strength, endurance, movement and EMG activity correlation was fair (r > 0.4, p < 0.001), as was PFM strength, endurance and abdominal muscle function (r > 0.4, p < 0.05). Conclusion: Movement impairment of local and global stability and mobility functions of PFM and abdominal muscles was present, as well as correlations between these functions. Addressing these impairments may affect the identified contextual factors (socio-economic, psychological and lifestyle factors) and the possible activity limitations and participation restrictions in patients with POP. Further research is needed to investigate these interactions. Clinical implications: The findings suggest that assessment and management of patients with POP might need to be based on a comprehensive neuro-musculoskeletal assessment and a holistic approach. Standardised protocols for patients with pelvic floor dysfunction (PFD) should therefore be used with caution. Randomised controlled trials should investigate patient-specific and holistic intervention approaches.